Development of lens-based probe designs and methods for depth-sensitive optical measurements - Ong, Yi Hong (2015)
This dissertation presents a series of studies on the development of non-contact lens based optical probe designs and data analysis methods for depth sensitive optical measurements, particularly Raman and fluorescence measurements, in skin pigmentary disorders. A method of Biochemical Component Analysis was developed first to decompose and fully utilize the entire Raman spectra in elucidating the biochemical basis of Raman spectra which can be used for identification of tissue malignancy and evaluation of treatment outcome in pigmentary disorders. The algorithm was validated in a cell death model study using K562 cell lines. Then, a novel cone shell illumination and detection configuration was introduced to enhance the depth sensitivity of conventional lens-based optical systems which employ a cone illumination and detection configuration. A Monte Carlo code was developed to simulate and investigate the depth sensitivity achieved by various combinations of illumination and detection configurations including both cone and cone shell configurations. Phantom experiments have been carried out to validate Monte Carlo modeling of fluorescence propagation in a two-layered turbid, epithelial tissue model. To evaluate the cone shell illumination and detection configuration experimetally, an axicon lens-based probe was designed and constructed, which eliminated the need of altering probe-sample distance in performing depth measurements. The probe was evaluated for depth-sensitive optical measurements in terms of the sensitivity to the top and bottom layer in a two layered turbid skin phantom. It was found that the axicon lens-based probe has enhanced the sensitivity to the bottom layer compared to that of an objective lens based probe with the cone configuration, and a larger range of sensitivity to either the top and bottom layer. After that, we improved the spectra acquisition speed of the axicon lens based setup by incorporating five rings of collection fibers into the detection configuration. The acquisition speed of the probe was improved by five times in which optical spectra from five different depths can be collected simultaneously in a single measurement. The new setup got rid of the mechanical moving part consisting of two axicon lenses that are required to achieve depth sensitive measurements. The performance of this improved setup was evaluated in a fluorescence study using a two layered turbid tissue phantom. In order to expand our depth sensitive optical probe from a point measurement system to an imaging system with a larger field of view, we demonstrated a multifocal noncontact setup capable of performing depth sensitive fluorescence imaging on a two-layered epithelial tissue model. The combination of a microlens array and a tunable lens enabled the depth of the multifocal plane to be conveniently adjusted without any mechanical movement of the imaging lens or sample. The performance of this improved setup was evaluated in a fluorescence imaging study by using a two-layered turbid tissue phantom and the result was further confirmed by spectral measurements. In summary, the depth-sensitive optical probes and the data processing algorithm we developed are able to extract layer-specific information from turbid media, which is clinically useful for the diagnosis and treatment evaluation of skin pigmentary disorders. Further improvement of these techniques would help advance the use of optical spectroscopy in clinical settings.